Implementation of Ventilation Panel Installation: Implementasi Instalasi Panel Ventilasi - Rifandi, Ahmad; Wisaksono, Arief (Procedia of Engineering and Life Science, 2024)
Abstract. Electrical panels are an important component in industry, which provides security to electrical installations in various industrial sectors. Large-scale companies dominate this industry to meet the high needs of consumers and maintain the quality and security of electrical installations. Electric panels must be installed carefully, pay attention to the surrounding environment, and play an important role in controlling ventilation to regulate the temperature and air conditions inside the cage. This research uses qualitative methods to understand the process of making ventilation panels. The results cover two types of panels: electric panels and ventilation panels. Electric panels serve as storage for electrical components, protect from the surrounding environment, and facilitate the operation of electrical machines. Meanwhile, ventilation panels are a crucial part of modern farm management, adjusting temperature and humidity to suit the needs of animals. The components in the ventilation panel involve various elements such as MCBs, TORs, contactors, relays, busbars, and others. The process of creating ventilation panels includes steps such as sketching pictures, making electrical panel boxes, assembling components, busbar assembly, wiring, as well as QA and QC stages to ensure panel quality. This process ends with finishing and packing before delivery to the consumer. This research provides an in-depth understanding of the manufacture of ventilation panels, which is essential for modern industry and agriculture inining optimal environmental conditions.